Abe Sapien : the drowning. [1] - Mignola, Mike (Dark Horse Books, 2008)
Abe Sapien (mainstay of Hellboy and B.P.R.D.) is ill-prepared for the dark forces that block his way to retreiving a warlock's remains. This story is Abe Sapien's first solo adventure.